2012
DOI: 10.1177/0960327112444476
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DNA polymorphisms in key DNA base excision repair proteins on cancer risk

Abstract: Genetic variation in DNA repair genes can modulate DNA repair capacity and may be related to cancer risk. However, study findings have been inconsistent. Inheritance of variant DNA repair genes is believed to influence individual susceptibility to the development of environmental cancer. Reliable knowledge on which the base excision repair (BER) sequence variants are associated with cancer risk would help elucidate the mechanism of cancer. Given that most of the previous studies had inadequate statistical powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
73
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 96 publications
0
73
1
2
Order By: Relevance
“…In BER systems, there are eleven DNA damage special proteins that contribute to a specific function. Among these components, X-ray repair cross-complementing group 1 (XRCC1) participates in the BER system (9,10). Another significant molecule, excision repair cross-complementation 1 (ERCC1), which encodes an ERCC1 protein, is involved in the NER pathway, eliminating significant DNA damage generated through environmental agents including toxic compounds or ultraviolet (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In BER systems, there are eleven DNA damage special proteins that contribute to a specific function. Among these components, X-ray repair cross-complementing group 1 (XRCC1) participates in the BER system (9,10). Another significant molecule, excision repair cross-complementation 1 (ERCC1), which encodes an ERCC1 protein, is involved in the NER pathway, eliminating significant DNA damage generated through environmental agents including toxic compounds or ultraviolet (10).…”
Section: Introductionmentioning
confidence: 99%
“…Among these components, X-ray repair cross-complementing group 1 (XRCC1) participates in the BER system (9,10). Another significant molecule, excision repair cross-complementation 1 (ERCC1), which encodes an ERCC1 protein, is involved in the NER pathway, eliminating significant DNA damage generated through environmental agents including toxic compounds or ultraviolet (10). Genetic variations, such as single nucleotide polymorphism (SNP) may exchange amino acids or modify DNA conformations, which is related to cancer risk or human disorders (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…However, Hsu et al (2015) found no significant association between XRCC1 gene polymorphisms and skin cancer risk, although in a case-control study, Zhu et al (2015) demonstrated that individuals carrying the Arg194Trp variation in this gene are more susceptible to prostate cancer. Several investigators have scrutinized the association between XRCC1 gene polymorphisms and gastric cancer risk, but their results have been inconsistent (Yan et al, 2009;Engin et al, 2011;Yuan et al, 2011;Karahalil et al, 2012;Pan et al, 2012;Wen et al, 2012). In Turkish populations, Engin et al (2011) and Karahalil et al (2012) found a statistically significant association between the XRCC1 Arg399Gln gene polymorphism and gastric cancer risk in Turkish populations.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have scrutinized the association between XRCC1 gene polymorphisms and gastric cancer risk, but their results have been inconsistent (Yan et al, 2009;Engin et al, 2011;Yuan et al, 2011;Karahalil et al, 2012;Pan et al, 2012;Wen et al, 2012). In Turkish populations, Engin et al (2011) and Karahalil et al (2012) found a statistically significant association between the XRCC1 Arg399Gln gene polymorphism and gastric cancer risk in Turkish populations. Wen et al (2012), Pan et al (2012), andYuan et al (2011) revealed a significant relationship between the Arg194Trp variant and susceptibility to this disease among Chinese individuals, while Yan et al (2009) reported that Arg399Gln and Arg194Trp sequence alterations have no effect, but the Arg280His polymorphism significantly increases gastric cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies have linked single nucleotide polymorphisms (SNPs) in BER pathway genes-increased human cancer risk including breast cancer which have been evaluated in different populations in past by focusing on three key genes: X-ray repair cross-complementing protein 1 (XRCC1), 8-oxoguanine DNA glycosylase (OGG1) and apurinic/apyrimidinic endonuclease 1(APEX1) (Hu et al, 2001;Zhang et al, 2006;Lo et al, 2009;Lu et al, 2009;Li et al, 2011;Karahalil et al, 2012;Mahjabeen et al, 2013;Kim et al, 2013;Popanda et al, 2013 ). APEX1 is multifunctional protein playing an important role in DNA repair process through AP-endonucleolytic 3' phosphodiesterase, 3'-5' exonuclease and 3' phosphatase activities.…”
Section: Discussionmentioning
confidence: 99%